Replacing Churches and Mason Lodges? Tax Exemptions and Rural Development - Luc Behaghel; Adrien Lorenceau; Simon Quantin (Institute for the Study of Labor (IZA), 2013)
This paper uses regression discontinuity design to provide quasi-experimental estimates of the impact of a tax credit program targeted at rural areas in France, including corporate and payroll tax exemptions. We find no impact of the program on total employment or the number of businesses, and no impact of the different program components on targeted subsets of firms. Comparison with a contemporaneous urban scheme suggests ways the incentives of the rural program could be targeted more effectively.
Keywords: J23; J32; H32; 330; tax exemptions; rural development; enterprise zones